Penerapan Pendekatan SFBC untuk mengurangi kebiasaan menyontek siswa kelas XI di SMA Negeri 8 Pinrang - Nasrullah Nasrullah (Universitas Negeri Makassar, 2022)
This study aims to reduce the habit of cheating in clas XI students at SMA Negeri 8 Pinrang throught group counseling services using the SFBC approach the method used is quantitative research using counseling quidance action research using. Which takes place in 3 cycles. The subjects of the research were students who had a high habit of cheating in class XII of SMA Negeri 8 Pinrang. Data collection techniques used questionnaires, observations and interviews. The data analysis method used is to analyze the success rate or percentage of giving reinforcement to students cheating habits. The results showed that group counseling using the SFBC approach could reduce the habit of cheating in class XI students at SMA Negeri 8 Pinrang